Assessment of potential predictors of calretinin and mesothelin to improve the diagnostic performance to detect malignant mesothelioma: results from a population-based cohort study. Issue 10 (11th October 2017) - Casjens, Swaantje; Weber, Daniel G; Johnen, Georg; Raiko, Irina; Taeger, Dirk; Meinig, Carmen; Moebus, Susanne; Jöckel, Karl-Heinz; Brüning, Thomas; Pesch, Beate
Abstract : Objectives: Mesothelin and calretinin are blood-based markers for malignant mesothelioma. The objective of this study was to analyse the markers in plasma samples from cancer-free men and to identify factors influencing their concentrations to minimise false-positive test results when using these markers for the early detection of malignant mesothelioma. Setting: The present analyses used data and archived blood samples of the population-based Heinz Nixdorf Recall Study among elderly people collected from 2011 to 2014. Participants: A total of 569 men (median age 70 years) without a malignant disease at the time of blood sampling were selected for these analyses. Primary and secondary outcome: Mesothelin and calretinin concentration in plasma samples. Results: We observed 24 mesothelin concentrations ≥1.5 nM (specificity 95.8%, 95% CI 93.8% to 97.2%) and 34 calretinin concentrations ≥1.0 ng/mL (specificity 94.0%, 95% CI 91.7% to 95.7%). Only five men had both markers above these cut-offs. Renal dysfunction and hypertension were major predictors of elevated mesothelin in addition to age. Regarding calretinin, the effect of renal dysfunction was slightly weaker and hypertension was not associated with increased concentrations. However, a diagnosis of cancer after blood collection and bronchial asthma were associated with positive calretinin results. Conclusions: The combined determination of mesothelin and calretinin results in only few false-positive marker tests. Both markers are mainly influenced by renal dysfunction. The determination of cystatin C concentrations may be informative when interpreting the test results.